2010
DOI: 10.1371/journal.pntd.0000846
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection with Different Trypanosoma cruzi Strains Interferes with the Host Immune Response to Infection

Abstract: A century after the discovery of Trypanosoma cruzi in a child living in Lassance, Minas Gerais, Brazil in 1909, many uncertainties remain with respect to factors determining the pathogenesis of Chagas disease (CD). Herein, we simultaneously investigate the contribution of both host and parasite factors during acute phase of infection in BALB/c mice infected with the JG and/or CL Brener T. cruzi strains. JG single infected mice presented reduced parasitemia and heart parasitism, no mortality, levels of pro-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 35 publications
2
35
0
3
Order By: Relevance
“…90 The length of acute parasitemia is highly variable among T. cruzi-infected vertebrate hosts, with some hosts exhibiting long-lasting high parasitemias and others moving from an acute stage to a chronic stage with low parasitemia in a matter of weeks. 1,88,89 In spite of all of this attention to the varied effects of T. cruzi on vertebrate hosts, until now, there has been relatively little attention to variation in its effect on its invertebrate hosts.…”
Section: Discussionmentioning
confidence: 99%
“…90 The length of acute parasitemia is highly variable among T. cruzi-infected vertebrate hosts, with some hosts exhibiting long-lasting high parasitemias and others moving from an acute stage to a chronic stage with low parasitemia in a matter of weeks. 1,88,89 In spite of all of this attention to the varied effects of T. cruzi on vertebrate hosts, until now, there has been relatively little attention to variation in its effect on its invertebrate hosts.…”
Section: Discussionmentioning
confidence: 99%
“…This specific F2 population was generated by intercrossing littermates derived from the breeding of the highly susceptible A/J with the highly resistant C57BL/6 mouse strains. Divergence in susceptibility to T. cruzi infection has been previously reported for different inbred mouse strains [19], [23], [30][33]. In studies specifically addressing the susceptibility to the Y strain of T. cruzi , it has been shown that mice from the A/J inbred strain succumb to infection, whereas C57BL/6 mice survive to the acute phase when infected with low inoculum (∼1000 forms) [22], [23].…”
Section: Resultsmentioning
confidence: 95%
“…In the infection by T. cruzi, both early interaction between the host cell and the parasite and the development of a suitable microenvironment of cytokines are critical aspects in controlling parasitemia (Rodrígues et al, 2010). In this sense, the efficiency of the microbicidal function depends on the participation of proinflammatory cytokines produced by NK, Th1 cells and macrophages, among others.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, lower synthesis of this cytokine was observed in V-I animals in relation to I animals. It is known that IL-10 neutralizes the function of TNF ␣ and regulates the synthesis of metalloproteases, IFN␥, IL-6, and NO (Rodrígues et al, 2010;Hovsepian et al, 2013). However, it is postulated that an excessive production of IL-10, particularly in early stages, might be, among other factors, responsible for the susceptibility to infection by T. cruzi (Basso et al, 2004).…”
Section: Discussionmentioning
confidence: 99%